IMPLEMENTATION OF TASK BASED – LEARNING IN TEACHING SPEAKING AT STKIP PGRI SUMBAR - analido, belinda (Kopertis Wilayah X (Sumbar, Riau, Jambi, dan Riau Kepulauan), 2016)
AbstrakStudents’ ability in expressing ideas is still far from expectation. It is found that several students have lack of vocabulary and grammar understanding. The purpose of the research is to analyze how well the participant implements task - based learning. This research was case study. The researcher collected the data through observation and used observation checklist and field note. Findings of the research is the participant applies various tasks in teaching speaking and integrates all of skills. Keywords: Task Based-Learning, Teaching Speaking